Improved Design of LNG Marine Loading Arm Docking Method Based on TRIZ Theory - Jie Mei; Wuwei Feng; Zirong Liang (Applied Sciences, 2023)
The LNG marine loading arm is a critical component for transferring LNG from vessels to onshore receiving stations. However, currently, the operation of LNG marine loading arms is still faced with issues such as a slow docking speed and significant environmental impacts from waves and wind. In this paper, we propose a set of feasible improvement schemes for the traditional LNG marine loading arm based on the theory of inventive problem solving (TRIZ). We utilized tools such as functional models, causal chain analysis, contradiction analysis, and Su-Field model analysis to develop these schemes. Our proposed improvements include using machine vision and automatic control to replace manual work, conducting finite element analysis and topology optimization of the LNG marine loading arm to improve its structure, and innovating the design of the end structure of the LNG discharge arm.